2017
DOI: 10.29303/jpft.v3i2.365
|View full text |Cite
|
Sign up to set email alerts
|

Model Inkuiri Terbimbing Berbantuan Multimedia Interaktif Untuk Meningkatkan Penguasaan Konsep Fisika Peserta Didik

Abstract: -The purpose of this study is to examine the effectiveness of learning use the guided inquiry model with interactive multimedia toward mastery of concept physics students. The study involved 68 students who were divided into two groups, the experimental group and control group. The research instrument used a mastery of concept physics students. Data were analyzed by using normalized gain scores. The result showed an increase in mastery of concept physics in both groups but experimental have the high increase m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
1
5
0
8
Order By: Relevance
“…So it can be concluded that there is an effect of using the 3D Pageflip Professional electronic student worksheet on the Protists concept on the cognitive learning outcomes of students in grade X of high school. Yulianci et al (2017) stated that learning with interactive multimedia, learning outcomes from students who use it are better than not using it. The process that students experience during the learning process can affect the success of students on product cognitive tests.…”
Section: Product Cognitive Learning Outcomesmentioning
confidence: 99%
“…So it can be concluded that there is an effect of using the 3D Pageflip Professional electronic student worksheet on the Protists concept on the cognitive learning outcomes of students in grade X of high school. Yulianci et al (2017) stated that learning with interactive multimedia, learning outcomes from students who use it are better than not using it. The process that students experience during the learning process can affect the success of students on product cognitive tests.…”
Section: Product Cognitive Learning Outcomesmentioning
confidence: 99%
“…Pembelajaran dengan menggunakan multimedia interaktif memungkinkan peserta didik untuk fokus pada konten, multimedia interaktif memuat unsurunsur media secara lengkap yang meliputi audio animasi, video, teks, dan grafis yang memungkinkan pengguna untuk berinteraksi secara interaktif melalui fitur-fitur yang tersedia [10].…”
Section: Pendahuluanunclassified
“…Integrasi TIK dalam pembelajaran memiliki banyak bentuk bergantung dengan spesifikasi dan tujuan masing-masing. Seperti simulasi virtual (Arianti et al 2017), multimedia interaktif (Yulianci, Gunawan, and Doyan 2017), dan laboratorium virtual (Sugiana et al 2017) yang dapat membantu siswa meningkatkan penguasaan konsep. Media pembelajaran berbasis Moodle juga berperan dalam membantu siswa memahami konsep fisika yang abstrak (Herayanti et al 2018).…”
Section: Pendahuluanunclassified